Seluk beluk Studi Kosa Kata dari Aspek Bentuknya - Ishak, Suhaimi (An Nazhair: Journal of Arabic Education, 2024)
Vocabulary is an important component in language acquisition. The study of vocabulary from its form aspect provides a deeper understanding of the structure and formation of words in a language. This research aims to explore and describe the intricacies of Indonesian vocabulary from the aspect of its form. The research method used is a descriptive qualitative approach. Data is analyzed by identifying, classifying, and describing vocabulary forms based on aspects of their form, such as basic words, derivative words, compound words, and other forms. The results of this research provide a comprehensive picture of the diversity of vocabulary forms in Indonesian, as well as providing a deeper understanding of the word formation process and its relationship with semantic and pragmatic aspects. The findings from this research can be useful for vocabulary development, language learning, as well as linguistic studies in general.